Metastatic HPV‐related oropharyngeal carcinoma cured with chemoradiotherapy: importance of pretherapy biomolecular assessment - Perri, Francesco (Clin Case Rep, 2017)
Pretherapy assessment has a crucial role in the management of advanced oropharyngeal carcinoma. The case report represents an example of how translational research may help to optimize the therapeutic options and to choose a well‐shaped therapy adapted to the tumor and the patient.